Analysis of Surface Integrity in Electrical Discharge Machining (EDM) Process for Tungsten Carbide Material - Khatter, Chander Parkash (My University, 2010)
The present work comprises of study conducted with a view to optimise the process parameters for machining of tungsten carbide (WC-Co) composite by EDM process. In order to improve MRR and also the surface roughness (R value), pulse-on time, the discharge current, electrode material and type of flushing were varied. The conclusions derived from the investigations are reported as below under separate heads.
Ph.D.
Keywords: EDM, Surface intrigity, Tungsten carbide